PUTATIVE DRUG TARGETS IN UREAPLASMA UREALYTICUM SEROVAR 10 STR. ATCC 33699 BY INSILICO GENOMICS APPROACH AND VIRTUAL SCREENING - VIJAYAKUMARI MALIPATIL; SHIVKUMAR MADAGI (International Journal of Pharma and Bio Sciences, 2013)
Increase in biological data at an alarming rate, has made possible the use of such data in identification of drug targets. Ureaplasma urealyticum serovar 10 str. ATCC 33699 is a causative agent for sexually transmitted infections. In present study novel comparative genomic approach is used to identify the drug targets. This approach has been successfully used in Pseudomonas aeroginosa. In current study similar work has been done to mine the drug targets. Analysis in the present study showed a total of 265 essential proteins, out of which 14 showed pathways related to both human and pathogen. The 2 proteins are exclusively pathogen specific and are part of unique metabolic pathways. The 3-D structure of the drug targets was predicted by fold based method and virtual screening was performed to find the natural lead compounds that bind to target. ADME-tox properties of the natural compounds showing better binding affinity were also studied.